Survival disparities following surgery among patients with different histological types of non-small cell lung cancer. (February 2020) - Grosu, Horiana B.; Manzanera, Andrea; Shivakumar, Sudeep; Sun, Simon; Noguras Gonzalez, Graciela; Ost, David E.
Highlights: Stage I squamous cell carcinoma has a high risk of mortality. Sage I squamous cell carcinomas have a higher mortality rate than those with adenocarcinoma. Addition of histological subtype may enhance traditional TNM classification. Abstract: Objectives: Clinical decisions for NSCLC patients are often based on TNM stage, which does not account for different histological subtype. Whether histological subtype affects survival still remains unclear. The main objective of this study was to determine the extent to which the survival outcomes of patients with early-stage NSCLC differ by histological subtype. Material and methods: Retrospective cohort study of SEER data base. Patients with stage IA and IB NSCLC that underwent surgery with lymph node dissection were included. The primary outcome was the time to death. Cox proportional hazards models were used to identify risk factors associated with overall survival (OS). The secondary outcome was the time to death from lung cancer. A Cox model and a Fine-Gray subdistribution hazards model in which death from causes other than lung cancer was considered a competing risk event were used to identify risk factors for death from lung cancer. Results: Analysis of the SEER database identified 28, 584 NSCLC patients, of whom 19, 750 (69 %) had adenocarcinoma and 8834 (31 %) had squamous cell carcinoma. In the multivariate for OS, older age (p < 0.001), male gender (p < 0.001), pneumonectomy (p < 0.001), larger tumor size (p < 0.001), squamous cell carcinoma (p < 0.001) not being Hispanic or Asian were associated with increased risk of death. In the competing risk model, older age (p < 0.001), male gender (p < 0.001), pneumonectomy (p < 0.001), larger tumor size (p < 0.001), and squamous cell carcinoma (p < 0.001) were was associated with an increased risk of death from lung cancer. Conclusion: This study suggests that among patients with stage I NSCLC, those with squamous histology have a higher risk of mortality than those with adenocarcinoma histology taking into account competing risks.